Osteoclast differentiation from circulating mononuclear precursors in Paget's disease is hypersensitive to 1,25-dihydroxyvitamin D(3) and RANKL. - Neale, S; Smith, R; Wass, J; Athanasou, N (2000)
A characteristic feature of Paget's disease is an increase in the number of osteoclasts in bone. Osteoclasts are formed from mononuclear phagocyte precursors that circulate in the monocyte fraction of peripheral blood. These cells require the presence of RANK ligand (RANKL)-expressing osteoblastic cells and human macrophage colony-stimulating factor (M-CSF) to form osteoclasts in vitro. To determine the role of osteoclast differentiation from circulating precursors in Paget's disease, we cultured monocytes from Paget's patients and gender- and age-matched normal controls with no evidence of bone disease for up to 21 days in the presence of UMR 106 cells and various concentrations of M-CSF (1-25 ng/mL) and 1,25-dihydroxyvitamin D(3) [1,25(OH)(2)D(3)] (10(-10) to 10(-7) mol/L). Relative to controls, there was a significant increase in the extent of osteoclast differentiation from pagetic monocytes as assessed by expression of tartrate-resistant acid phosphatase (TRAP), vitronectin receptor (VNR), and lacunar bone resorption. Serial dilution experiments (2 x 10(5) to 2 x 10(2) cells/well) showed no difference in the concentration of osteoclast precursors in the peripheral blood. In Paget's patients with high serum alkaline phosphatase (sAP) levels, increased sensitivity to the osteoclastogenic effect of 1,25(OH)(2)D(3) was noted. Osteoclast differentiation did not occur when M-CSF was substituted by interleukin-6 (IL-6) and soluble IL-6 receptor (sIL-6R), and these factors did not stimulate osteoclast differentiation in the presence of M-CSF. In this in vitro coculture system, osteoclast formation was inhibited by osteoprotegerin in a dose-dependent manner. In the presence of RANKL (5-30 ng/mL) and M-CSF (25 ng/mL), osteoclast formation and bone resorption were significantly increased in cultures of monocytes from patients with high and low sAP levels as compared with normal controls. Our findings suggest that the increase in osteoclast numbers seen in Paget's disease results not from an increase in the number of circulating precursors in peripheral blood but rather from an increased sensitivity of osteoclast precursors to the humoral factors, 1,25(OH)(2)D(3) and RANKL, which regulate osteoclast formation.